Sastera sebagai seismograf kehidupan (Kuala Lumpur Dewan Bahasa dan Pustaka, Kementerian Pendidikan Malaysia, 1993)
Literary criticism of Malay literature.
At head of title: Edisi khas sasterawan negara.
Includes bibliographical references and index.
Keywords: Malay literature -- 20th century -- History and criticism